Penerapan Proses Restorative Justice Melalui Pendekatan Restorative Conferencing Initiatives Di Indonesia - Noya, Melva; Toule, Elsa Rina Maya; Tuhumury, Carolina (Faculty of Law, Universitas Pattimura, 2021)
Introduction: The Restorative Converencing Initiative is a criminal settlement system that involves perpetrators, victims and related parties, in this way it is hoped that it can solve a crime with the aim of returning everything to its original state.Purposes of the Research: know how to apply the restorative conference initiative process in Indonesia and second, the author wants to examine the process of applying the restorative conference method in the criminal justice system in Indonesia.Methods of the Research: The research method used is Normative-Empirical legal research, the problem approach used is a conceptual approach using primary, secondary legal materials, qualitative analysis.Results of the Research: The results show that Restorative Converencing Initiatives are not something new in Indonesia. Long before the country became independent, indigenous groups had already resolved legal problems using the Restorative Converencing Initiatives. It's just that for naming according to the development of the legal world, then we are familiar with the term Restorative Converencing Initiatives. The settlement process varies according to prevailing customs and social systems in the community group. The basis for conflict resolution using the Converencing Initiatives method is to maintain a balance and kinship in the community.